A Pengaruh Kuat Tekan dan Daya Serap Air Laut Pada Material Komposit Sandwich Serat Sabut Kelapa - Jayadin; Muhammad Mujiburohman; Handik Hendratama; Tri Widayatno; Nur Arifah Hidayati; Hamzarudin Hikmatiar (Jurnal Teknik Mesin Indonesia, 2025)
The need for boards as a material for furniture is increasing, therefore alternative materials are needed to replace wooden boards, such as sandwich composite boards. Coconut is a tropical plant that has long been known by Indonesian people. Coconut is one of the plants that can be used as a composite board, namely coconut fiber. This research aims to make composite boards from coconut fiber to determine the compressive strength and absorption capacity of sea water. The materials for this research are coconut fiber and polyester resin. Coconut fiber is a waste that is rarely used so the waste can become serious waste. This research uses the Compressing Molding method at room temperature where the mold is loaded. In this research, compression testing uses ASTM D 659 standards and seawater absorption testing uses ASTM D 570 standards. The results of this research show optimal conditions at a volume fraction of 20% with a core thickness of 6 mm, namely 8,230 MPa in compression testing and 25% thickness. The 8 mm core in the Sea Water Absorption Capacity test had the lowest absorption capacity at 0.16%.